Intravascular Imaging During Percutaneous Coronary Intervention: JACC State-of-the-Art Review - Truesdell, Alexander G; Alasnag, Mirvat A; Kaul, Prashant; Rab, Syed Tanveer; Riley, Robert F; Young, Michael N; Batchelor, Wayne B; Maehara, Akiko; Welt, Frederick G; Kirtane, Ajay J (Journal of the American College of Cardiology, 2023)
Coronary angiography has historically served as the gold standard for diagnosis of coronary artery disease and guidance of percutaneous coronary intervention (PCI). Adjunctive use of contemporary intravascular imaging (IVI) technologies has emerged as a complement to conventional angiography-to further characterize plaque morphology and optimize the performance of PCI. IVI has utility for preintervention lesion and vessel assessment, periprocedural guidance of lesion preparation and stent deployment, and postintervention assessment of optimal endpoints and exclusion of complications. The role of IVI in reducing major adverse cardiac events in complex lesion subsets is emerging, and further studies evaluating broader use are underway or in development. This paper provides an overview of currently available IVI technologies, reviews data supporting their utilization for PCI guidance and optimization across a variety of lesion subsets, proposes best practices, and advocates for broader use of these technologies as a part of contemporary practice.